Is Japan really changing its ways?: (Brooking Institution Press, 1988)
The book also examines the nuts-and-bolts issues of reforms in major economic sectors and the implications of deregulation for access to Japanese markets for foreign imports. By focusing on both the larger political, economic, and strategic contexts and on the way in which the micro and macro aspects of regulatory reform are interconnected, this volume makes comprehensible the tidal wave of proposals and posturing coming out of Japan.